High rates of human fecal carriage of mcr-1-positive multi-drug resistant Enterobacteriaceae isolates emerge in China in association with successful plasmid families - Zhong, L; Phan, H; Shen, C; Vihta, K; Sheppard, A; Huang, X; Zeng, K; Li, H; Zhang, X; Patil, S; Crook, D; Walker, A; et al. (Oxford University Press, 2017)
Objectives mcr-1-mediated colistin resistance in Enterobacteriaceae is concerning, as colistin is used in treating multidrug-resistant Enterobacteriaceae infections. Rates of human mcr-1 gastrointestinal carriage have historically been low. We identified trends in human fecal mcr-1-positivity rates and colonization with mcr-1-positive+third-generation cephalosporin-resistant (3GC-R) Enterobacteriaceae in Guangzhou, China, and investigated the genetic contexts of mcr-1 in a subset of mcr-1-positive+3GC-R strains. Methods Fecal samples were collected from in-patients and out-patients submitting specimens to three hospitals (2011-2016). mcr-1 carriage trends were assessed using iterative sequential regression. A subset of mcr-1-positive isolates was sequenced (whole genome sequencing [WGS], Illumina), and genetic contexts (flanking regions, plasmids) of mcr-1 characterized. Results Of 8,022 fecal samples collected, 497 (6.2%) were mcr-1-positive, and 182 (2.3%) harbored mcr-1-positive+3GC-R Enterobacteriaceae. We observed marked increases in mcr-1 (0% [Apr/2011] to 31% [Mar/2016]) and more recent (since January 2014; 0% [Apr/2011] to 15% [Mar/2016]) increases in human colonization with mcr-1-positive+3GC-R Enterobacteriaceae (p<0.001). mcr-1-positive+3GC-R isolates were commonly multi-drug resistant. WGS of mcr-1-positive+3GC-R isolates (70 Escherichia coli, 3 Klebsiella pneumoniae) demonstrated bacterial strain diversity (48 E. coli sequence types); mcr-1 in association with common plasmid backbones (IncI, IncHI2/HI2A, IncX4) and sometimes in multiple plasmids; frequent mcr-1 chromosomal integration; and high mobility of the mcr-1-associated insertion sequence ISApl1. Sequence similarity with published mcr-1 plasmid sequences was consistent with spread amongst animal/human reservoirs. Conclusions The high prevalence of mcr-1 in multidrug-resistant E. coli colonizing humans is a clinical threat; diverse genetic mechanisms (strains/plasmids/insertion sequences) have contributed to the dissemination of mcr-1, and will facilitate its persistence.